Spread of bacterial wilt disease on potato in three villages in Silimakuta District, Simalungun, North Sumatra, Indonesia - Nahrisa Rahmadhani; Mukhtar Iskandar Pinem; Irda Safni (Universitas Lampung, 2022)
Bacterial wilt disease caused by Ralstonia syzygii subsp. indonesiensis is an important disease in potatoes. This disease is a soil-borne pathogen that is difficult to control and becomes an obstacle in potato production. This study aimed to determine the distribution of bacterial wilt disease in potatoes caused by R. syzygii subsp indonesiensis in three villages in Silimakuta District, Simalungun Regency, North Sumatra. This research was exploratory research that was conducted using a survey method by calculating the incidence of disease in potatoes in 9 locations from three villages. The results showed that the intensity of bacterial wilt occurred with different percentages of disease incidence. The highest disease incidence of 100% was in Sibangun Meriah Village Location 2 and the lowest disease incidence of 22,5% was in Saribu Dolok Village Location 1.